PENGEMBANGAN PROMOSI DESA EKOWISATA BURAI OGAN ILIR MELALUI PELATIHAN KOMUNIKASI PARIWISATA - Pratiwi, Miftha; Andarini, Rindang Senja; Astuti, Misni; Karerek, Karerek (Universitas Mataram, 2025)
Burai Ecotourism Village in Ogan Ilir has transformed from a slum into a leading tourist destination in South Sumatera. However, its digital tourism promotion remains underdeveloped, particularly through Instagram. The lack of understanding in tourism communication and digital content creation is a major barrier to increasing tourist visits, requiring training to improve sustainable promotion capacities among local tourism stakeholders. This activity aims to enhance participants’ understanding of tourism communication and digital promotional skills using Instagram as a strategic platform. The method involved a three-day program consisting of socialization and Focus Group Discussions (FGDs) with 40 participants, including tourism managers, POKDARWIS and MSMEs. The results showed a 79% increase in participants’ knowledge after receiving training on basic tourism communication and photography. Participants practiced photo and video conten creation using mobile phones and editing applications such as Lightroom and Capcut. Hands-on activities strengthened their digital promotion capacity and raised awareness of the importance of visual branding. Pre-test and Post-test evaluations revealed a significant improvement in promotional communication skills. The training effectively improved participants’ digital tourism promotional skills.